Pogonatherumol, a Novel Highly Oxygenated Norsesquiterpene with Flavone C-Glycosides from Pogonatherum crinitum - Lin Ni; Wei Huang; He-shan Wang; Hui-you Xu (Journal of Chemistry)
A novel highly oxygenated norsesquiterpene, pogonatherumol (1), with two known flavone C-glycosides (2-3), was isolated from Pogonatherum crinitum. The structure of the new compound was illuminated based on its spectroscopic data and X-ray analysis. Compounds 1 and 3 inhibited NO production in the mouse peritoneal macrophage (64.5 ± 7.2% and 61.6 ± 5.8%, respectively, at a concentration of 50 μM). The three compounds were inactive when tested against two human cancer cell lines (IC50 values > 50 μM).